Utilization of complementary and alternative medicine among Korean elite athletes: Current status and future implications - Youn, B.-Y.; Ju, S.; Joo, S.; Kang, H.; Jeon, K.; Cheon, C.; Go, H.-Y.; Ko, S.-G. (Evidence-Based Complementary and Alternative Medicine, 2021)
The objective of the study was to explore the status of usage of complementary and alternative medicine (CAM) among Korean elite athletes. A survey was emailed to all Korean national sports federations recognized by the International Olympic Committee and the Olympic Council of Asia. A total of 705 Korean elite athletes participated in this study. The athletes had to be any of the following to participate in this survey: elite intercollegiate athletes, professional athletes, and national team athletes. 83.3% of the participants stated that they have previously experienced Korean medicine (KM). Compared to the general population in Korea, athletes had more experience (general population = 73.8%). The participants without experience mentioned that they either did not need any KM treatments (39.8%) or lacked information (39.8%) regarding KM treatments. The primary reason for the utilization of KM was the effectiveness of treatments. Therefore, 70.8% of the participants have mentioned recommending KM to others. Generally, athletes are worrisome that the consumption of herbal medicine may not be doping-free; however, it is vital to note that 62% of the participants expressed that prescribed herbal medicine is safe. Overall, this research demonstrates a high prevalence of KM usage by intercollegiate, professional, and national team athletes in Korea. Hence, this study`s results may serve as the foundation in future research directions for promoting KM among Korean elite athletes.